(untitled) (Scientia Agropecuaria, 2020)
The objective of the present study was to evaluate the extraction and microencapsulation of antioxidant compounds from Oenocarpus bataua Mart seed, commonly known as “ungurahui” or “patawa”. The extraction process was performed in an ultrasonic bath and the orthogonal composite central design of the response surface methodology (RSM) was used to determine the optimal extraction conditions, using two factors: ethanol concentration (48.44 to 91.56%) and extraction time (13.83 to 46.17 min). The optimal extraction conditions (48.44% ethanol and 13.83 min) allowed to obtain the extract (EUL) with the highest number of antioxidants (yield (YI): 24.64%, total phenolic content (TPC): 452.76 mg GAE/g EUL and DPPH: 74.26%). Microencapsulation of EUL with maltodextrin by spray drying produced microcapsules (EUM) of homogeneous size (5 µm), without cracks or fissures and that preserved its antioxidant capacity (TPC: 110.08 mg GAE / g EUM, DPPH: 74.59%) because the encapsulant protected the core from being affected by drying temperature. The microcapsules also showed no significant degradation during storage. In general, this study offers a suitable process for the incorporation of antioxidant compounds from Oenocarpus bataua seed in the food industry.